Synthesis, structure and coordination chemistry of new monopodal and bipodal thiocarbamic esters and acyl(aroyl)-substituted ureas with Ni(II), Pd(II), Pt(II) and Cu(II) - Blewett Gavin (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2006.